Manutenção das faces em feedbacks: uma análise das estratégias de polidez utilizadas por tutores na formação continuada de gestores escolares na modalidade Educação a Distância - Messias, Tiago Monteiro de (2022)
This thesis has as its theme the politeness strategies used to maintain the faces of the interactants in texts of the feedback genre produced in a process of continuing education of educators in blended learning modality. We justify this choice because the feedback brings imminent risks to the faces of the interactants. In this sense, the speaker seeks to preserve his face and that of his interlocutor in written feedbacks, in the distance learning modality, being able to resort to elements of politeness in the interaction. We hypothesize that the speaker uses politeness strategies to create a positive and close context with his interlocutor, in order to foster a collaborative and valuing image, making it possible to preserve the face of the interactants. The research questions that guide this study are: 1) What are the politeness strategies used by the speakers in these texts? and 2) What contributions can this study bring to the production of feedbacks conveyed in distance education environments? To answer them, the general objective is: to evaluate the politeness strategies used by the speakers to preserve the faces of the interactants in feedbacks produced in the process of continuing education in the distance education modality. In order to meet this objective, we have chosen the following specific objectives: a. identify, list, describe and interpret the politeness strategies recurrently used by the speakers in the feedbacks; B. to list perspectives for the construction of feedbacks produced in blended learning training contexts, based on politeness elements. The present work, with a qualitative approach, is characterized as a documental research based on its theoretical-analytical basis. The theoretical contribution that subsidizes us comes from: the studies of Goffman (2014[1967]; 2014[1974]); of the contributions of Brown e Levinson (1987), Kerbrat-Orecchioni (2017), Marlangeon (2017) and Seara and Cabral (2017); about face work and politeness; with regard to ethos and its construction, we are guided by studies of Maingueneau (2008) and Charaudeau (2016); in the field of Textual Linguistics, notably the studies of Beaugrande and Dressler (1981), Cavalcante et al. (2010), Fávero and Koch (2012), Koch (1997; 2004; 2015), Marcuschi (1998; 2008), Marquesi (2014), and Van Dijk (1977, 1983, 1989); regarding the assumptions of Textual Analysis of Discourses - TDA, we resort to Adam (2010; 2011; 2019), Passeggi et al. (2010), Marquesi, Elias and Cabral (2017), Sparano et al. (2012), Página11 as well as the notions of text plan, Koch (2014), Koch e Elias (2009), Marquesi, Elias e Cabral (2017), Marquesi et al. (2019); regarding the modalities, we enrolled studies of Bronckart (2003), Castilho e Castilho (2002), Cervoni (1989), Charaudeau (1992), Comparini (1991), Dubois (1969), Ducrot (1987), Fiorin (2000), Fleischman (1982), Gasparini-Bastos (2014), Halliday (2004), Le Querler (1996), Lyons (1977; 2009), Koch (2011), Nascimento (2005), Nascimento and Silva (2012), Neves (2006), Neves (2007), Olbertz and Gasparini-Bastos (2013), Palmer (1986) and Nascimento (2007; 2009). The results obtained reveal that the use of politeness strategies by the speakers, for the maintenance of the faces, can strengthen the interaction between the interactants, enhancing the training process. In addition, the collected inputs make it possible to map a set of politeness strategies that strengthen purposeful and cautious communication, supporting tutors in achieving the objectives proposed in the training process, mediated by the feedback genre